Use of stock market instruments as a way to support small and medium-sized businesses during economic crises - K. V. Gluhov; M. V. Shipilova (Вестник университета)
This study determines the possibilities of using stock market instruments as a source of financing for small and medium-sized businesses during the COVID-19 coronavirus crisis, as well as developing proposals for expanding the system of public support measures to popularise this mode of financing. The authors put forward a hypothesis that the stock market is an effective tool for small and medium-sized businesses to use in times of crisis, but that it is rarely used at the moment. The existing methods of state support for small and medium-sized businesses using stock market instruments have been systematised and reviewed. The procedure for granting subsidies to small and medium-sized businesses has been defined and the procedure for selecting issuers has been highlighted. Foreign experience of supporting small and medium-sized businesses through the stock market, using the United States and Polish examples, has been studied. The difficulties encountered by entrepreneurs in using the stock market instruments in Russia have been analysed and proposals for overcoming them have been made. Conclusions have been made on the effectiveness of this way of supporting small and medium-sized businesses in a difficult economic situation. A proposal to expand the system of state support and popularise this method of financing among small and medium-sized businesses has been formulated.